Efeitos do campo elétrico cristalino nos compostos isoestruturais ErM4Al8 (M = Cu, Fe) - Santos, Barbeny de Jesus (2023)
In this work, the effects of the crystalline electric field on the isostructural compounds of ErM4Al8 (M = Cu and Fe) were investigated. The samples were produced by arc furnace melting. X-ray diffraction measurements (XRD) confirmed the presence of a single phase with a tetragonal structure of type ThMn12 and space group I4/mmm. A spin model based on the solution of the crystalline electric field Hamiltonian was used to extract the crystalline field parameters, the wave functions and build a level scheme, from magnetization measurements as a function of the magnetic field and temperature. The X-ray diffraction analyzes show that the global and local symmetry do not change for the samples grown with copper and iron and, in addition, the average distances between the ions remain the same. On the other hand, crystal field parameters vary appreciably from one sample to the next. This fact was related to the change in the electronic structure of the transition metal ions. Calculations based on first principles show that the d-electrons from the iron go to the Fermi surface and thus must contribute an electrostatic shielding effect to the crystalline electric field when compared to the sample grown with copper.